Designing New Financial Management System in Health Sector of Islamic Republic of Iran - R Hafezi; M Abolhallaje; M Ramezanian (Tehran University of Medical Sciences, 2009)
"nBackground: In health system of any country, securing financial resources and management of the same is one of the most vital apprehensions in regards policy makers. This article expresses a part of the obstacles and threats present in the management of the government financial resources of health sector and in assimilating this, the requirement for amendments in the financial system and designing new financial management system of health sector in Iran."nMethods: The authors conducted a case study based on interviews with government, and academic participants. Two methods of data collection were used: retrospective analysis of official documents and in-depth interview."nResults: The root of the obstacles relevant to the management of financial resources in health sector in four intricate and fundamental modes of executing cash accounts in contrary to accrual accounts, where there is an intense weakness in the internal controls due to the lack of periodic reports, so as to define the source of deviations, the lack of a mechanized system and ultimately, the absence of a comprehensive monetary plan in the Country. Based on these obstacles, the new financial management system of health sector in Iran was designed including mission, objectives, structure, human resources and duties, processes and procedures, external environment."nConclusion: Designing new financial system in health sector of country is a way to effective and efficient management of financial resources and aid health system to achieve ultimate goals.